Combined HAT/EZH2 modulation leads to cancer-selective cell death - Petraglia, Francesca; Singh, Abhishek A.; Carafa, Vincenzo; Nebbioso, Angela; Conte, Mariarosaria; Scisciola, Lucia; Valente, Sergio; Baldi, Alfonso; Mandoli, Amit; Petrizzi, Valeria Belsito; Ingenito, Concetta; De Falco, Sandro; et al. (Oncotarget, 2018)
Epigenetic alterations have been associated with both pathogenesis and progression of cancer. By screening of library compounds, we identified a novel hybrid epi-drug MC2884, a HAT/EZH2 inhibitor, able to induce cancer-selective cell death in both solid and hematological cancers , and xenograft models. Anticancer action was due to an epigenome modulation by H3K27me3, H3K27ac, H3K9/14ac decrease, and to caspase-dependent apoptosis induction. MC2884 triggered mitochondrial pathway apoptosis by up-regulation of cleaved-BID, and strong down-regulation of BCL2. Even aggressive models of cancer, such as p53 or TET2 cells, responded to MC2884, suggesting MC2884 therapeutic potential also for the therapy of TP53 or TET2-deficient human cancers. MC2884 induced massive apoptosis in human primary leukemia blasts with poor prognosis , by targeting BCL2 expression. MC2884-treatment reduced acetylation of the BCL2 promoter at higher level than combined p300 and EZH2 inhibition. This suggests a key role for BCL-2 reduction in potentiating responsiveness, also in combination therapy with BCL2 inhibitors. Finally, we identified both the mechanism of MC2884 action as well as a potential therapeutic scheme of its use. Altogether, this provides proof of concept for the use of epi-drugs coupled with epigenome analyses to 'personalize' precision medicine.